WEB BASED ONLINE FOOD SALES INFORMATION SYSTEM (CASE STUDY OF WARUNG BEBEK SRUNDENG SEDATI) - Ferro Jala Satria Putra; Suprianto Suprianto (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to design and develop a Web-Based Online Food Sales Information System for Warung Bebek Sedati to improve the efficiency of buyer queues and order management processes. The current manual recording system has proven to be ineffective, causing delays and difficulties in tracking customer orders. Method: The research employs a system development approach using the PHP programming language and MySQL as the database management system. The design focuses on simplifying transactions between buyers and sellers by enabling online ordering and automated order recording. Results: The developed system successfully facilitates buyers in placing food orders online and allows the stall to monitor and manage order data in real time without manual input. The system implementation significantly reduces queuing time and enhances service efficiency. Novelty: The innovation of this study lies in integrating a real-time web-based ordering and queue management system tailored for small-scale food businesses, providing a practical technological solution to improve service quality and sales performance in traditional food stalls.